Regional Economic Outlook : Sub-Saharan Africa, October 2007. (World economic and financial surveys., 2007)
The region's prospects look strong. Growth in sub-Saharan Africa should reach 6 percent in 2007 and 6℗ℓ percent in 2008. The economic expansion is strongest in oil exporters but cuts across all country groups. This would extend a period of very good performance. In recent years, sub-Saharan Africa has been experiencing its strongest growth and lowest inflation in over 30 years.